ANALISIS PERILAKU KONSUMEN DALAM PEMBELIAN PRODUK SAYURAN DI PASAR MODERN KOTA BEKASI - Dasipah, Euis; Budiyono, Haris; Julaeni, Meilan (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2010)
This research was conducted to know what type of vegetables most desired by consumers those are sold in the supermarket, the characteristic of consumer behavior and those faktors could influence consumer to decide to get vegetables in the supermarket. Consumer samples was purposively chosen in four representative supermarket in the city of Bekasi. Those consumer respondents were asked to express their motives to buy vegetables in the supermarket by Questionnaire. The result shows that vegetables buyers were 89% woman and 11% man. The respondents varied 26-35 years old (41%), 36-45 years old (34%) and 15-25 years old (25%). The respondents have married (73%) and single (27%) By educational level, they were grouped 75% high education degree and senior high school 25%. By status of work, 43% (housewives), 37% (private works), 10% (entrepreneur) and 10% (state officers). Their income varied 46% (Rp. 2.000.000 – 3.000.000), 24% (Rp. 3.000.000 – 4.000.000), 18% (< Rp. 2.000.000), 10% (Rp.4.000.000 – 5.000.000) and 2% (>Rp 5.000.000). their family level 1-4 person (67%) and >4 person (33%). The most desired vegetables by consumers in the supermarket were spinach, broccoli, carrot, sweet maize, and the white mustard. The intensity of shopping for vegetables were only on special purposed (45%), weekly (22%), twice in a month (18%) and monthly (15%). The total money spent for vegetables shopping were 37% (Rp. 25.000 – 50.000). The data were analyzed to list 14 variables which influence the respondent to shopping vegetables in the supermarket by using SPSS 12.0. those variables were grouped into 4 groups. The first group were field of job (0.867), status and role (0.782), phase and age (0.757) and knowledge (0.705). the second group were family (0.749), life style (0.740), reference by group (0.660) and demography (0.6210. the third group were personality (0.794), perception (0.790), motivation (0.745) and confidence (0.636). the fourth group were economic welfare status (0.841) and social class (0.792).